Safety evaluation of the food enzyme subtilisin from the genetically modified Bacillus licheniformis strain NZYM‐CB - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The food enzyme subtilisin (EC 3.4.21.62) is produced with the genetically modified Bacillus licheniformis strain NZYM‐CB by Novozymes A/S. The genetic modifications do not give rise to safety concerns. The food enzyme is considered free from viable cells of the production organism and its DNA. It is intended to be used in six food manufacturing processes. The dietary exposure to the food enzyme‐TOS was estimated to be up to 0.722 mg TOS/kg body weight (bw) per day in European populations. The production strain of the food enzyme fulfils the requirements for the qualified presumption of safety approach to safety assessment. As no other concerns arising from the manufacturing process were identified, the Panel considered that toxicological tests were not required for the assessment of this food enzyme. A search for the similarity of the amino acid sequence of the food enzyme to known allergens was made and 20 matches were found, including two food allergens (melon and pomegranate). The Panel considered that the risk of allergic reactions by dietary exposure cannot be excluded, particularly in individuals sensitised to melon and pomegranate, but would not exceed the risk from consumption of melon or pomegranate. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.